2016
DOI: 10.4028/www.scientific.net/msf.879.714
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Weldability of Titanium Alloy Ti-6Al-4V and Aluminum Alloy 6061 Produced by Electron Beam Welding

Abstract: Aluminum and titanium alloys are among the most important and the most frequently used construction materials due to their physical and mechanical properties. Especially in the automotive and aerospace industry these materials allow to reduce the weight of structure which leads to reducing fuel consumption and environment pollution. These materials are often used together which leads to problems with junction between these materials. In addition to the mechanical joints, there is an effort to produce quality w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Therefore, the intermetallic structures within the welded joint are greatly reduced, as in the present particular case; they are in the form of a very thin layer at the interface between the Ti and Al alloys. As mentioned in the introduction, the authors of [38] studied the weldability of the Ti6Al4V and 6061-Al alloys. The results showed that the application of an offset strongly influences the phase composition and hardness of the obtained joint, where the maximum offset was 0.3 mm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the intermetallic structures within the welded joint are greatly reduced, as in the present particular case; they are in the form of a very thin layer at the interface between the Ti and Al alloys. As mentioned in the introduction, the authors of [38] studied the weldability of the Ti6Al4V and 6061-Al alloys. The results showed that the application of an offset strongly influences the phase composition and hardness of the obtained joint, where the maximum offset was 0.3 mm.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the structure investigated in Ref. [38] for a welded joint in which the beam has been shifted towards the Al alloy is much wider and consists of a large number of intermetallic phases, which is expected to lead to a deterioration in the functional properties. Therefore, the application of a larger offset (two times larger than the beam spot in the present case) to the material with the lower melting point and higher thermal conductivity has a major importance and plays a very important role in the reduction of the intermetallic structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Havlík et al conducted a study on the weldability of the Ti-6Al-4V/AA 6061 dissimilar joint obtained by the electron beam process by varying the beam offset. The author reported the presence of Ti3Al, TiAl, Ti5Al11 and Ti3Al5 as well as volume fraction of IMCs controlled by the offset variation [16].…”
Section: Introductionmentioning
confidence: 99%
“…The authors mentioned that higher impact toughness was achieved with the EBW process, and grain growth due to thermal cycles was minimum in both cases. Havlik et al [29] investigated the microstructure behavior of ferritic steel, martensite steel, and austenite steel using an EBW process and mentioned that the solidification rate of the WZ controls the final formation of the microstructure. The grain size was smaller for higher cooling rates [30].…”
Section: Introductionmentioning
confidence: 99%